Microfluidic fabrication of vesicles with hybrid lipid/nanoparticle bilayer membranes. Issue 6 (10th January 2019) - Perrotton, Julie; Ahijado-Guzmán, Rubén; Moleiro, Lara H.; Tinao, Berta; Guerrero-Martinez, Andrés; Amstad, Esther; Monroy, Francisco; Arriaga, Laura R.
Abstract : Water-in-oil-in-water double emulsion drops, fabricated using capillary microfluidics, enable the formation of vesicles with hybrid lipid/nanoparticle membranes. Abstract : Hybrid lipid/nanoparticle membranes are suitable model systems both to study the complex interactions between nanoparticles and biological membranes, and to demonstrate technological concepts in cellular sensing and drug delivery. Unfortunately, embedding nanoparticles into the bilayer membrane of lipid vesicles is challenging due to the poor control over the vesicle fabrication process of conventional methodologies and the fragility of the modified lipid bilayer assembly. Here, the utility of water-in-oil-in-water double emulsion drops with ultrathin oil shells as templates to form vesicles with hybrid lipid/nanoparticle membranes is reported. Moreover, upon bilayer formation, which occurs through dewetting of the oil solvent from the double emulsion drops, a phase separation is observed in the vesicle membrane, with solid-like nanoparticle-rich microdomains segregated into a continuous fluid-like nanoparticle-poor phase. This phase coexistence evidences the complex nature of the interactions between nanoparticles and lipid membranes. In this context, this microfluidic-assisted fabrication strategy may play a crucial role in thoroughly understanding such interactions given the uniform membrane properties of the resulting productions. Furthermore, the high encapsulation efficiency of both the vesicle membrane and core endows these vesicles with great potential for sensing applications and drug delivery.